Feasibility study of coke combustion and energy exergy analysis in the De-Coke process of cracking furnaces in olefin unit - Mostafa Moshtagh; Ahmad Azari; Marziyeh Hoseinpour; Rouhollah Fatehi; Farhad Ghadyanlou; Rahim Karami; Mohammad Rasul; Mohammad Akrami (Scientific Reports)
Abstract This study investigates the numerical simulation of cracking furnaces and the feasibility of coke combustion in the De-Coke flow, utilizing computational fluid dynamics (CFD) and energy-exergy analysis. Employing the Euler-Lagrange approach, we simulate the motion of coke particles within the model. A turbulent model is applied to assess the combustion processes, while non-premixed models simulate fuel and coke particle interactions. Additionally, we incorporate the Discrete Ordinates Model for radiation and the Discrete Phase Model for coke particle motion simulation. Results indicate that injecting coke particles with dry air leads to a 100% conversion rate. However, increasing the temperature of the De-Coke stream from 454 K to 654 K yields only a slight increase in coke conversion from 52 to 55%, suggesting that sufficient time and temperature are crucial for complete combustion. The energy and exergy efficiency of the combustion furnace during the cracking process stand at 44.8% and 29%, respectively, compared to 93.24% and 96.2% during the coil cracking process. Furthermore, the destruction exergy for the combustion furnace is approximately 36%, whereas the coil experiences destruction exergy of less than 4%. Although energy and exergy distributions reveal similar trends for both conventional and burning-coke De-Coke processes at the coil, the burning-coke method offers increased destruction exergy and enhanced heat transfer, albeit at the cost of efficiency in energy and exergy transfer to the coil compared to conventional methods.